A plasmid-encoded peptide from Staphylococcus aureus induces anti-myeloperoxidase nephritogenic autoimmunity - Ooi, JD; Jiang, J-H; Eggenhuizen, PJ; Chua, LL; van Timmeren, M; Loh, KL; O'Sullivan, KM; Gan, PY; Zhong, Y; Tsyganov, K; Shochet, LR; Ryan, J; et al. (Nature Research, 2019)
Autoreactivity to myeloperoxidase (MPO) causes anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV), with rapidly progressive glomerulonephritis. Here, we show that a Staphylococcus aureus peptide, homologous to an immunodominant MPO T-cell epitope (MPO409–428), can induce anti-MPO autoimmunity. The peptide (6PGD391–410) is part of a plasmid-encoded 6-phosphogluconate dehydrogenase found in some S. aureus strains. It induces anti-MPO T-cell autoimmunity and MPO-ANCA in mice, whereas related sequences do not. Mice immunized with 6PGD391–410, or with S. aureus containing a plasmid expressing 6PGD391–410, develop glomerulonephritis when MPO is deposited in glomeruli. The peptide induces anti-MPO autoreactivity in the context of three MHC class II allomorphs. Furthermore, we show that 6PGD391–410 is immunogenic in humans, as healthy human and AAV patient sera contain anti-6PGD and anti-6PGD391–410 antibodies. Therefore, our results support the idea that bacterial plasmids might have a function in autoimmune disease.